Kajian Produksi Kunci Penahan Pulley Transmisi Sepeda Motor Matik - Mochammad Habibi; Syamsul Hadi; Andah Lugas Dhinata; Tambah Sutrisno (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2025)
The problem lies in the difficulty of locking the pulley retainer on automatic motorcycle transmissions without using a special Y-shaped key. The purpose of the study is to obtain a special pulley retainer lock product on automatic motorcycle transmissions that can be adjusted the distance between the two retaining pins through adjusting bolts with easy and effective locking steps. The study method includes the design of the pulley retainer lock component formation, the selection of stainless steel pulley retainer lock materials, the production of pulley retainer lock components through flat and curved forging, turning the handle, forming a Y-shaped lever pair plate, drilling 2 holes at the ends of the lever, drilling the Y-shaped auxiliary tool opening and closing pins, and drilling the Y-shaped auxiliary tool opening distance adjustment bolts, assembling the components that form the pulley retainer lock, and testing the use of the pulley retainer lock. The production results are in the form of a special pulley archery key with a total length of 300 mm, the maximum opening distance on the axis of 2 pens is 110 mm, the length of 2 pen tips is 7 mm with a total pen length of 30 mm, and one diameter is 9 mm with a total pen length of 30 mm, the adjusting bolt for the opening angle of the pulley retaining key measures M6x20 mm, and the diameter of the Y-shaped tool rivet pen used is 6 mm.